Incidence of Mastitis in the Neonatal Period in a Traditional Breastfeeding Society: Results of a Cohort Study. - Khanal, Vishnu; Scott, Jane; Lee, Andy; Binns, Colin (2015)
Background: Mastitis is a painful problem experienced by breastfeeding women, especially in the first few weeks postpartum. There have been limited studies of the incidence of mastitis from traditionally breastfeeding societies in South Asia. This study investigated the incidence, determinants, and management of mastitis in the first month postpartum, as well as its association with breastfeeding outcomes at 4 and 6 months postpartum, in western Nepal. Subjects and Methods: Subjects were a subsample of 338 mothers participating in a larger prospective cohort study conducted in 2014 in western Nepal. Mothers were interviewed during the first month postpartum and again at 4 and 6 months to obtain information on breastfeeding practices. The association of mastitis and determinant variables was investigated using multivariable logistic regression, and the association with breastfeeding duration was examined using Kaplan–Meier estimation. Results: The incidence of mastitis was 8.0% (95% confidence interval, 5.1%, 10.8%) in the first month postpartum. Prelacteal feeding (adjusted odds ratio = 2.76; 95% confidence interval, 1.03, 7.40) and cesarean section (adjusted odds ratio = 3.52; 95% confidence interval, 1.09, 11.42) were associated with a higher likelihood of mastitis. Kaplan–Meier estimation showed no significant difference in the duration of exclusive breastfeeding among the mothers who experienced an episode of mastitis and those who did not. Conclusions: Roughly one in 10 (8.0%) women experienced mastitis in the first month postpartum, and there appeared to be little effect of mastitis on breastfeeding outcomes. Traditional breastfeeding practices should be encouraged, and the management of mastitis should be included as a part of lactation promotion.